'Under my wing': exploring the connection between generativity and mentoring through storytelling. Issue 4 (8th August 2022) - Sunderman, Hannah M.; Mccain, Kate D.; Hastings, Lindsay J.
ABSTRACT: The purpose of the current study was to explore the connection between generativity and mentoring. Specifically, ten college students who mentor shared stories illustrating the link they perceived between mentoring and generativity. A cross-case analysis was utilized to explore the data and connect the developmental/environmental factors of leader identity (i.e. motivations to mentor) with generative themes (i.e. how participants mentored or were mentored). The cross-case analysis resulted in three overarching mentoring styles: Guide, Relator, and Friend. Findings from the current study have implications for leadership educators, mentoring programs, and college student development scholars.